Analysis of Assistive Technology Needs for Inclusive Education in the Early Childhood Education Development Sector of the East Kutai Regency Education Office - Achmad Yoyon; Hermanto Hermanto (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the need for assistive technology to support inclusive education in early childhood education institutions in East Kutai Regency. The main focus includes educators' understanding of assistive technology, identification of the types of technology needed, availability of facilities and infrastructure, and obstacles faced in implementing inclusive learning for students with special needs. The approach used is descriptive quantitative with a survey design. The research subjects consisted of teachers and early childhood education staff directly involved in inclusive learning. Data collection was carried out through the distribution of questionnaires and documentation of assistive technology policies and facilities. The instruments used measured teachers' understanding, availability of facilities, and the need for assistive technology. Data were analyzed using descriptive statistics in the form of frequencies and percentages. The results of the study indicate that although teachers' understanding of assistive technology is relatively high, their technical skills in using assistive devices are still limited. The availability of facilities and infrastructure is at a moderate level, and not all institutions have adequate devices. The main obstacles include limited infrastructure and minimal social support. This study recommends technical training, strengthening inter-institutional collaboration, and policies and budget allocations that support the optimal use of assistive technology in inclusive early childhood education.